The Ability of PAUD Teacher Education Students to Develop a Cheese Roll Culinary Business to Increase the Entrepreneurial Spirit in the 4.0 Revolution Era - Sari, Octarina Mayang; Yuliandari, Izzazur Rohmah (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2023)
Entrepreneurship is a mental attitude and spirit that is always active, creative, inventive, initiative and modest in trying to increase income in business activities. Someone who has an entrepreneurial spirit and attitude always feels dissatisfied with what he has achieved. Business is one of the main activities in supporting economic development. Here we take the culinary business "cheese roll". Culinary is defined as the process of making food. This term is not from Indonesian but from English, namely culinary, which means the technique of cooking, processing and serving food. From this background, the researchers conducted research with the aim of knowing the ability of PAUD Teacher Education students in developing a Cheese Roll Culinary Business to Increase Entrepreneurial Spirit in the 4.0 Revolution Era. The research method used is the literature study research method. The research was conducted for 2 months. From this research, it is known that the Cheese Roll business in terms of ideas, market targets, financial plans in the form of capital, and others, has promising prospects in the future. The biggest challenge in the marketing and promotion of this Cheese Roll product is the many competitors with similar products. Therefore, the target market for this business must be right on target and convincing.